Food culture and wisdom of the Tai Lue ethnic group Lamphun Province - Chompuja, Sungwan; Srikaeo, Khongsak; Sornnoey, Keeratiya; Trongtorkit, Wanpen; Kaewsritong, Jiraphat (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2025)
This research aimed to study the history, culture and food wisdom of the Tai Lue ethnic group in Ban Thi Subdistrict, Ban Thi District, Lamphun Province, and to develop a food set of the Tai Lue Ban Thi ethnic group. This was a qualitative research using a structured interview with 27 people who provided information on Tai Lue culture and food wisdom using a chain selection method, in-depth interviews and focus group discussions, and content analysis. The research results found that the history of the Tai Lue people showed migration, settlement, village expansion, and the preservation of cultural identity, especially the food culture that combines simplicity and the use of local ingredients available in the area. They eat 3 meals, each consisting of steamed sticky rice and curry and chili paste for almost every meal. Beef is preferred over pork. The taste emphasizes saltiness from grains of salt and sourness from ripe tamarind. Sweetness is not preferred. The spiciness is moderate. There is an informal form of food culture transmission from learning from ancestors and exchanging knowledge within the community. The results of the development of 3 food sets, each set consisting of 5-6 savory items, sticky rice, chili paste, and various vegetables as ingredients in every set. There is 1 sweet dish, Khao Tom Hua Ngok.